KONSTRUKSI BERITA SEPAKBOLA ANALISIS FRAMING FINAL “LIGA CHAMPIONS” MUSIM 2013-2014 PADA MEDIA ONLINE OKEZONE.COM - Hamdani Junan; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
One of online media’s strength that is compared with conventional media, like newspaper, is its fastness in reporting news. Meanwhile, news release tendency of online media as same as conventional media is influenced by Ideology and importance of the media. This research was aimed to find out the framing analysis of football news release especially Champions league final in 2013-2014 season at Okezone.com online media. This research is a qualitative research that used framing analysis approach of Pan and Kosicki model (in Eriyanto, 2008).The data collection techniques were documentation, interview, online data collection (internet searching) and study of related literature. There are five news that were analyzed in this research. These news represented about everything happened before, during and after the final match. Based on the study that used agenda setting theory, media politic economy and framing elements of Pan and Kosicki model, the research findings show that news release framing of Okezone.com media online tended to side with Real Madrid than Atletico Madrid. It could be seen from the number of headline that often show off Real Madrid’s other side, including condition of players and Real Madrid’s ambitious target to obtain La Decima. Besides, Okezone.com also placed Real Madrid in media product as the main commodity that proposes entertainment side which had trade value in order to gain the readers’ attention.Keyword :Online Media’s, Analysis Framing, Media Politic Economy